Video exoscope as a cost-effective alternative to surgical microscope in microsurgical subinguinal varicocelectomy in Indonesia: A case report - Daniel Amartya; Widi Atmoko; Gede Wirya Kusuma Duarsa; Dyandra Parikesit; Ponco Birowo (Urology Case Reports, 2023)
Microsurgical subinguinal varicocelectomy (MSV) is considered the preferred treatment for varicocele. However, its adoption among urologists in Indonesia is limited due to the high cost of acquiring a surgical microscope. Therefore, most varicoceles were managed using loupe-assisted MSV, which is considered a less effective approach. This paper presents a case study of a patient with bilateral grade II varicocele who underwent a successful MSV procedure using a video exoscope. The exoscope provided sufficient magnification and image quality for the safe and efficient performance of MSV on a patient.